PENGARUH JARIMATIKA TERHADAP KETERAMPILAN BERHITUNG PERKALIAN SISWA - Nasir, Satriana; Patta, Rahmawati; Riang Tati, Andi Dewi (STKIP Melawi, 2025)
Abstract: This study examined the effectiveness of the jarimatika method in developing multiplication skills in fourth-grade students at SD Inpres Nipa-Nipa. A total of 54 students (experimental group: fourth grade B, 27 students; control group: fourth grade A, 27 students) participated through non-random assignment. Data collection was conducted in stages through a pre-test, the jarimatika treatment in the experimental group, and a post-test. The experimental group's average score increased from 55.74 (poor category) in the pre-test to 84.63 (good category) in the post-test. The control group's average also rose from 67.41 (fair category) to 75.93 (good category). Statistical tests showed a significant difference between the groups (Sig. 0.032<0.05). In conclusion, jarimatika had a positive impact on students' multiplication skills. The contribution of this research is empirical evidence of the effectiveness of jarimatika as an alternative learning method and opens opportunities for further research. Keywords: Jarimatika, Multiplication, Counting Ability, Elementary School Students Abstrak: Studi ini meneliti efektivitas metode jarimatika dalam mengembangkan kecakapan berhitung perkalian pada siswa kelas IV SD Inpres Nipa-Nipa. Sebanyak 54 siswa (kelompok eksperimen: kelas IV B, 27 siswa; kelompok kontrol: kelas IV A, 27 siswa) berpartisipasi melalui penetapan non-acak. Penghimpunan data dilakukan berjenjang melalui pre-test, perlakuan jarimatika pada kelompok eksperimen, serta post-test. Rerata kelompok eksperimen meningkat dari 55,74 (kategori kurang baik) pada pre-test menjadi 84,63 (kategori baik) pada post-test. Rerata kelompok kontrol juga naik dari 67,41 (kategori cukup baik) menjadi 75,93 (kategori baik). Uji statistik menunjukkan perbedaan nyata antar kelompok (Sig. 0,032<0,05). Sebagai simpulan, jarimatika berdampak positif pada keterampilan berhitung perkalian siswa. Kontribusi riset ini adalah bukti empiris efektivitas jarimatika sebagai alternatif metode pembelajaran dan membuka peluang bagi riset lanjutan. Kata Kunci: Jarimatika, Perkalian, Kemampuan Berhitung, Siswa Sekolah Dasar.